2020
DOI: 10.21273/hortsci14515-19
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Uptake and Use Efficiency in Sweet Basil Production under Low Tunnels

Abstract: Low tunnels (LTs) enhance vegetative growth and production in comparison with open field, but it is not known whether nitrogen (N) requirements and use efficiency increase or decrease for optimal crop performance. Therefore, the purpose of this study was to determine differences in N requirement, uptake, and use efficiency in basil grown under LTs compared with open field. The experimental design each year was a split plot with four replications. The main effect (plots) was N fertilizer application rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Consumer demand for fresh, aromatic, functional, low-calorie food garnishes has allowed sweet basil to emerge as a growing market segment worldwide [2]. This species has become a high-income niche crop that for its fast production cycle can boost farm's cash flow as well as the profitability of hydroponics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumer demand for fresh, aromatic, functional, low-calorie food garnishes has allowed sweet basil to emerge as a growing market segment worldwide [2]. This species has become a high-income niche crop that for its fast production cycle can boost farm's cash flow as well as the profitability of hydroponics.…”
Section: Discussionmentioning
confidence: 99%
“…The total nitrogen accumulation in leaves was not different, reflecting the invariable N fertilization in the two phases. Nonetheless after the first cut, the leaf-level nitrogen use efficiency decreased, possibly because nitrogen concentration declines with leaf growth [2]. The higher nitrogen concentration of the leaves of the second cut has two main implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have considered that crop yield response can be estimated as a smooth, concave production function such as any quadratic form (Heady & Dillon, 1961;Segarra et al, 1989;Frank et al, 1990;Hurley et al, 2005;Roberts et al, 2006;Park, 2012;Xu et al, 2009;Harper et al, 2012). Historically, the quadratic form has been a standard specification for modeling crop yield to nutrients (Segarra et al, 1989;Cerrato & Blackmer, 1990;Boyer et al, 2012;Acharya et al, 2020).…”
Section: Quadratic Response Functionmentioning
confidence: 99%
“…Basil cultivation is conducted in open fields as well as under protected environments in both soil and soilless cultivation systems. Aiming to improve crop yield and to increase availability of basil leaves throughout the year, controlled cultivation in protective structures such as greenhouses is more appropriate than cultivation in an open field [ 16 , 17 , 21 , 22 ]. Previous studies where the N fertilization rate on basil plants was tested showed a positive effect on plant growth through a yield increase, although the higher crop production was not always accompanied with high quality for the final product [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%